Voice-based Dynamic Time Warping Recognition Scheme for Enhanced Database Access Security - Onoma, Paul Avweresuo; Ugbotu, Eferhire Valentine; Aghaunor, Tabitha Chukwudi; Agboi, Joy; Ojugo, Arnold Adimabua; Odiakaose, Christopher Chukwufunaya; Max-Egba, Asuobite ThankGod; Niemogha, Star Umiyemeromesu; Binitie, Amaka Patience; Abdullahi, Mustapha Barau (Peneliti Teknologi Teknik Indonesia, 2025)
Rapid transformation with database security has remained imperative as unauthorized access exposes sensitive data to adversaries. To curb this, we suggest using a secured dynamic time-warp scheme to improve access to the database schemas. The study integrates voice biometrics with two-factor authentication to yield a robust, user-friendly platform, which utilizes time-warping to authenticate voice patterns against the variability in utterance speed. Results showcase high accuracy and resiliency in its usage against spoofing attacks as compared to state-of-the-art voice recognition systems. The model ensures the minimal possibility of credential theft by binding the access of databases to the voice features of authorized users. The study shows the system's architecture, implementation, and performance evaluation, highlighting its potential to revolutionize database security in various applications. The findings underscore the importance of leveraging advanced biometric techniques to safeguard critical information systems.